2020
DOI: 10.1177/0963689720913876
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Specific Regulatory T Cell-Mediated Immune Tolerance in an Intrahepatic Murine Allogeneic Islet Transplantation Model with Short-Term Anti-CD154 mAb Single Treatment

Abstract: Anti-CD154 blockade-based regimens remain unequaled in prolonging graft survival in various organ transplantation models. Several studies have focused on transplantation tolerance with the anti-CD154 blockade, but none of these studies has investigated the mechanisms associated with its use as the sole treatment in animal models, delaying our understanding of anti-CD154 blockade-mediated immune tolerance. The purpose of this study was to investigate the mechanism underlying the anti-CD154 monoclonal antibody (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 72 publications
2
5
0
Order By: Relevance
“…However, C3H skin (third-party skin) rejection was comparable between islets + CsA microparticles + CTLA4-Ig treated recipients and control recipients. Our skin grafts results are consistent with previous reports whereby naïve B6 mice rejected BALB/c skin allografts at 14 days posttransplant whereas intrahepatic islet transplanted tolerant B6 mice showed a modest prolongation of skin allograft survival for up to 17 days posttransplant (19). Our observations, align with others that reported that tolerance to Fas ligand chimeric with streptavidin (SA-FasL)-engineered islet grafts is donor-specific and systemic at the induction phase.…”
Section: Discussionsupporting
confidence: 92%
“…However, C3H skin (third-party skin) rejection was comparable between islets + CsA microparticles + CTLA4-Ig treated recipients and control recipients. Our skin grafts results are consistent with previous reports whereby naïve B6 mice rejected BALB/c skin allografts at 14 days posttransplant whereas intrahepatic islet transplanted tolerant B6 mice showed a modest prolongation of skin allograft survival for up to 17 days posttransplant (19). Our observations, align with others that reported that tolerance to Fas ligand chimeric with streptavidin (SA-FasL)-engineered islet grafts is donor-specific and systemic at the induction phase.…”
Section: Discussionsupporting
confidence: 92%
“…Using a DEREG mouse model Lee et al. demonstrated that a short-term blockade of CD154 could lead to Treg mediated immune tolerance in the intrahepatic murine allogeneic islet transplantation model ( 196 ). Animal studies are supported by clinical data where CD154 blockade in relapsing-remitting multiple sclerosis patient demonstrated an increase of CD25+ T cells and anti-inflammatory cytokines ( 197 ).…”
Section: The Role Of Co-stimulatory Pathways In Treg Homeostasis and ...mentioning
confidence: 99%
“…Immune tolerance induction is a promising strategy to accept histocompatibility complex (MHC)-mismatched allografts without reducing resistance to infection or increasing other complications ( 67 ). For immunological tolerance to allografts, the high proportion of MHC alloreactive T cell is considered as a major barrier to tolerance induction.…”
Section: Immunosuppressive Drug Toxicity and Immune Tolerance Inductionmentioning
confidence: 99%
“…And in the intrahepatic mouse allogeneic islet transplantation model, Lee et al. demonstrated for the first time that short-term single administration of anti-CD154 monoclonal antibody could induce FoxP3+ Treg cell-mediated immune tolerance ( 67 ).…”
Section: Immunosuppressive Drug Toxicity and Immune Tolerance Inductionmentioning
confidence: 99%